1999
DOI: 10.1080/135048599352402
|View full text |Cite
|
Sign up to set email alerts
|

Long-run neutrality of money in the Mexican economy

Abstract: The long-run neutrality of money on real output is tested for Mexico using a model developed by Fisher and Seater. The empirical evidence supports the neutrality hypothesis. The results are robust for both M1 and M2 and an alternative model specification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…(2). 4 It is beyond the scope of the paper to investigate the reason(s) that removal of the first 39 months of data alters the specification so dramatically, but it may be due to unusual exchange rate or price level behavior caused by the removal of gold from circulation and the prohibition of the coinage of silver in Mexico during this period (see Wallace 1999 and sources cited therein). All estimation results reported below are for specifications of Eqs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2). 4 It is beyond the scope of the paper to investigate the reason(s) that removal of the first 39 months of data alters the specification so dramatically, but it may be due to unusual exchange rate or price level behavior caused by the removal of gold from circulation and the prohibition of the coinage of silver in Mexico during this period (see Wallace 1999 and sources cited therein). All estimation results reported below are for specifications of Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…His tests indicate mean reversion, evidence of PPP, in Mexico and most of the other countries studied. Several other studies have applied different stationarity tests to the Taylor data and find support for PPP in most countries including Mexico (Wallace and Shelley 2006;Bahmani-Oskooee et al 2007;Wallace 2008Wallace , 2013 As figure 1 in Ventosa et al shows, the Mexico-US real exchange has been volatile over the period , but the volatility is most pronounced in the decade beginning 1980 during which exchange rate controls were adopted and banks nationalized (Wallace 1999 provides a summary of events). VGW apply the Kim, Leybourne, and Newbold unit root test which is robust to volatility changes and find evidence of purchasing power parity for the Mexico-US real exchange rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This framework is highly sensitive to the order of integration: if the real variables are integrated of order 1, monetary variables should be integrated of order 2. Using this framework, some studies reported evidence in favor of the LRN conditions: Weber (1994) for the G-7 countries and Wallace (1999;2005) for Mexico and Guatemala. Telatar and Cavusoglu (2005) analyzed the LRN condition in the case of five high-inflation countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…model for Nicaragua following the Fisher-Seater (1993) methodology .The results indicate rejection of the hypothesis of LRSN both when output is aggregated and disaggregated. Wallace and Shelly (2007) examine LRSN in Mexico and conclude that the hypothesis of LRSN cannot be rejected. Sanchez-Fung (2010) tests the hypothesis of LRSN in the Dominican Republic using a cointegration approach.…”
Section: Introductionmentioning
confidence: 99%